Measuring Social Climate in German Prisons Using the Essen Climate Evaluation Schema - Schalast, Norbert (The prison journal, 2017)
Sociotherapeutic prison units have been criticized for their close operational connection with traditional prison systems. This research compared the social climate of German therapeutic prison units with that of traditional prison units, using the Essen Climate Evaluation Schema (EssenCES). The EssenCES was administered in conjunction with the shortened Correctional Institutions Environment Scale. Results indicate significant differences between therapeutic and traditional units’ social climates, with the former demonstrating more supportive, safe, and therapeutic climates. Findings further confirm the psychometric properties of the EssenCES and support its use as a social climate measurement instrument.